Performance of Okra under Drip Irrigation with Saline Water - Saxena, C. K.; Gupta, S. K.; Purohit, R. C.; Bhaka, S. R.; Upadhyay, B. (Journal of Agricultural Engineering, 2014)
A study was conducted at the research farm of Central Soil Salinity Research Institute, Karnal, to evaluate the effect of salinity of irrigation water on the yield of okra (Abelmoschusesculentus L. Moench) under drip irrigation. The experiment was conducted in randomized block design with 4 levels of saline irrigation water (ECiw = 0.2, 2.0, 4.0, 8.0 dS.m-1) in three replications. Significant change in the yield of okra (Var: Mahyco-10 Hy) was observed at 1% level of significance. It was found that even at 8 dS.m-1 irrigation water salinity, 77% of okra yield to the check could be obtained. Highest water use efficiency was with available fresh water of 0.2 dS.m at 0.49, and for the treatments of 2.0, 4.0, 8.0 dS.m-1 it was observed at 0.49, 0.46 and 0.38 t.ha-1.cm-1, respectively.